The Effectiveness of Village Funds for Community Empowerment Program - Wulan Bedi Pratama; Ira Wahyuni Syarfi; Hasnah Hasnah (International Journal of Agricultural Sciences, 2022)
This study aims to analyze the effectiveness of community empowerment using village funds in developed and developing villages. This research employed a survey method on multiple case studies involving 70 respondents. Data were analyzed using a quantitative approach. The results showed that the effectiveness of community empowerment program is more effective in the developed village. The variables of community awareness, participation, independence, and income have a positive and significant effect on the effectiveness of the community empowerment program.